2010
DOI: 10.1074/jbc.m110.100735
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Metabolite, All-trans-retinoic Acid, Mediates Alternative Splicing of Protein Kinase C δVIII (PKCδVIII) Isoform via Splicing Factor SC35

Abstract: Vitamin A metabolite, all-trans-retinoic acid (RA), induces cell growth, differentiation, and apoptosis and has an emerging role in gene regulation and alternative splicing events. Protein kinase C␦ (PKC␦), a serine/threonine kinase, has a role in cell proliferation, differentiation, and apoptosis. We reported an alternatively spliced variant of human PKC␦, PKC␦VIII that functions as a pro-survival protein (1). RA regulates the splicing and expression of PKC␦VIII via utilization of a downstream 5 splice site o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…This stands in contradiction to results of a recent study on mice [Bezy et al, 2011] in which PKCd was selectively knocked out either globally or in liver cells, or was overexpressed in the liver. One relates to the possibility that recently identified PKCd splice variants [Ueyama et al, 2000;Sakurai et al, 2001;Apostolatos et al, 2010] may have important influences on overall biological effects. This resulted in increased insulin-induced suppression of hepatic gluconeogenesis, improved glucose tolerance, and reduced hepatosteatosis with aging.…”
Section: Discussionmentioning
confidence: 99%
“…This stands in contradiction to results of a recent study on mice [Bezy et al, 2011] in which PKCd was selectively knocked out either globally or in liver cells, or was overexpressed in the liver. One relates to the possibility that recently identified PKCd splice variants [Ueyama et al, 2000;Sakurai et al, 2001;Apostolatos et al, 2010] may have important influences on overall biological effects. This resulted in increased insulin-induced suppression of hepatic gluconeogenesis, improved glucose tolerance, and reduced hepatosteatosis with aging.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PKCδ WT transgenic mice overexpressing PKCδ increased cytosolic accumulation of the cell cycle inhibitory p21 Cip1/WAF1 . Different splice variants of PKCδ involving in apoptosis (PKCδI) and pro-survival pathway (PKCδII and PKCδVIII) have also been reported [97, 98]. Patel et al [99] demonstrated that TRA2B regulated splice variants PKCδI is essential for clonal expansion of pre-adipocytes and its expression decreases with terminal differentiation.…”
Section: Role Of Protein Kinase C In Obesity and Insulin Resistancementioning
confidence: 99%
“…The stilbene (3,3Ј-[1,2-dimethyl-1,2-ethenediyl]bis Phenol) was purified upon silica gel chromatographic separation (76% yield). Construction of pSPL3-PKC␦ Minigene-The pSPL3 vector was modified to remove cryptic 5Ј splice sites as described in our previous publication (26). The pSPL3 vector was digested with BamHI (in the MCS) and NheI.…”
Section: Synthesis Of 33ј-[12-dimethyl-12-ethenediyl]bis Phenol-inmentioning
confidence: 99%